Review Artikel: Tanaman Obat yang Berpotensi terhadap Penyembuhan Luka Sayat - Kurnia, Aifa; Atifah, Yusni (Lembaga Yasin AlSys, 2024)
A wound is the loss or damage of part of the body's tissues. So far, standard handling of wounds on the skin carried out in the medical world is by giving antiseptics, antibiotics, and anti-inflammatory. Wound healing is a complex process so efforts to find an effective wound healing agent continue. Medical drugs that are constantly used sometimes have unwanted side effects, for that alternative drugs are needed to reduce side effects. Medicinal plants that have the potential to heal incision wounds are torch ginger umbut, binahong leaves, tampala steel stems, yellow turmeric rhizomes, ginger leaves, red ginger rhizomes, and cassava leaves. Various preparations from the plant have the potential to heal incision wounds.